2021
DOI: 10.1007/s00170-021-07034-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and tool wear of titanium alloy thread cutting in dry and cryogenic conditions

Abstract: The article is devoted to the study of the effect of cryogenic cooling on the tool wear in thread turning tests. The tool wear and its influence on the thread accuracy were investigated. Two different grades of titanium alloys were used for comparative purposes. The excellent performance characteristics of titanium alloys pose machining problems, causing high unit forces at the edge of the tool leading to chipping and premature tool failure. In turn, the low thermal conductivity of pure titanium affects the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Zawada-Tomkiewicz et al [6], titanium and its alloys can be considered difficult-to-cut materials due to the low thermal conductivity and their chemical reactivity at high temperatures. The titanium and its alloys are widely used in aerospace, medical science, and automobiles due to the low weight-tostrength ratio and high corrosive resistance, for example.…”
Section: Introductionmentioning
confidence: 99%
“…Zawada-Tomkiewicz et al [6], titanium and its alloys can be considered difficult-to-cut materials due to the low thermal conductivity and their chemical reactivity at high temperatures. The titanium and its alloys are widely used in aerospace, medical science, and automobiles due to the low weight-tostrength ratio and high corrosive resistance, for example.…”
Section: Introductionmentioning
confidence: 99%
“…With tool wear becoming the most serious problem of titanium alloy cutting, numerous studies have been conducted to analyze the wear mechanism and find methods to decrease the tool wear for extending the tool life. 5,[13][14][15][16][17][18][19][20][21][22] Pramanik et al 13 analyzed the causes of chip formation and tool wear in the cutting of titanium alloy and confirmed that the main factors of tool wear include plastic deformation, thermal cracking, abrasion and diffusion. Biermann et al 14 surveyed the cryogenic cutting process of two different titanium alloys and analyzed the different behavior and tool life in cutting processes under cryogenic conditions.…”
Section: Introductionmentioning
confidence: 99%